On the construction of committed consistent global states in optimistic simulation. (22nd September 2009) - Quaglia, Francesco
In this paper, we study how to reuse checkpoints taken in an uncorrelated manner during the forward execution phase in an optimistic simulation system in order to construct global consistent snapshots which are also committed, namely the logical time they refer to is lower than the current Global-Virtual-Time (GVT). Specifically, we present a heuristic-based mechanism relying on update operations applied to local committed checkpoints of the logical processes so to eliminate mutual dependencies among the final achieved state values. The mechanism is lightweight since it does not require any form of (distributed) coordination to determine which are the checkpoint update operations to be locally performed for each logical process. At the same time it is likely to reduce the amount of checkpoint update operations required to realign the consistent global state exactly to the current GVT, taken as the reference time for the snapshot. Our proposal can support, in a performance effective manner, termination detection schemes based on global predicates evaluated on a committed and consistent global snapshot, which represent an alternative as relevant as classical termination check only relying on the current GVT value.